2011
DOI: 10.1007/s00296-011-1929-4
|View full text |Cite
|
Sign up to set email alerts
|

TNFα-mediated apoptosis in human osteoarthritic chondrocytes sensitized by PI3K-NF-κB inhibitor, not mTOR inhibitor

Abstract: To investigate apoptosis of osteoarthritic (OA) chondrocytes stimulated with different inhibitors targeting tumor necrosis factor-alpha (TNFα) pathway, we isolated first passage chondrocytes from OA patients and then treated them with the inhibitors in combination with TNFα, and then collected the stimulated chondrocytes for Western blotting. Chondrocytes from OA patients expressed cleaved caspase-3 and PARP, suggesting apoptotic background. We here, validated that 10 ng/ml of TNFα couldn't induce more chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…NFκB signaling is the major signaling pathway activated by TNF-alpha in OA chondrocytes 37 , 38 . To understand whether the anti-inflammatory effect of BMMSC-EVs, could be mediated through the regulation of NFκB activity, we treated TNF-alpha-stimulated OA chondrocytes with BMMSC-EVs and analyzed the subcellular localization of the p65 subunit of NFκB.…”
Section: Resultsmentioning
confidence: 99%
“…NFκB signaling is the major signaling pathway activated by TNF-alpha in OA chondrocytes 37 , 38 . To understand whether the anti-inflammatory effect of BMMSC-EVs, could be mediated through the regulation of NFκB activity, we treated TNF-alpha-stimulated OA chondrocytes with BMMSC-EVs and analyzed the subcellular localization of the p65 subunit of NFκB.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, AG490, a pan-JAK SMI significantly reduced leptininduced chondrocyte apoptosis in vitro as well as reducing STAT3 phosphorylation, reactive oxygen species, MMP-13 and B-cell lymphoma 2-associated X protein [146]. Interestingly, Li et al [147] showed that the PI3K/NF-κB pathway was activated by TNF-α in human chondrocytes. However, the effect of leptin did not involve mTOR, suggesting that newly developed small molecule mTOR inhibitors (reviewed in [36]) might not be useful for neutralizing activated PI3K/NF-κB in response to leptin-induced apoptosis.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…Additionally, some of the agents that their combined using with TRAIL has been acceptable outcomes but in limited cell lines have been listed below. kurarinone (Seo et al, ; Zhou, Cao, Wang, & Wu, ), monensin (Yoon et al, ), paxiline (Kang et al, ), diclofenac/hyaluronic acid (Dic/HA) (Fecker et al, ), nickel2+ (Schmidt et al, ), SHetA2 (Lin et al, ), BAY 11–7085 (Shen et al, ), compound c (Jang et al, ), FAK inhibitor PH11 (Dao et al, ), caffeic acid phenethyl ester (CAPE) (Li, Wu, et al, ), fasudil (Wang et al, ), cathepsin S inhibitor ZFL (Seo et al, ), 4‐(4‐Chloro‐2‐methylphenoxy)‐N‐hydroxybutanamide (CMH) (Bijangi‐Vishehsaraei, Huang, Safa, Saadatzadeh, & Murphy, ), actinomycin (Haimerl, Erhardt, Sass, & Tiegs, ), H1 (derivative of tetrandrine) (Lin, Wang, et al, ), genistein (Siegelin, Siegelin, Habel, & Gaiser, ), icaritin (Han, Xu, et al, ), ABT‐737 and VX–680 (Choi et al, ), 6‐shogaol (Han, Woo, et al, ), cathepsin E (Yasukochi, Kawakubo, Nakamura, & Yamamoto, ), ozarelix (Festuccia et al, ), transglutaminase 2 inhibitor (TGM2I) (Li, Xu, Bai, Chen, & Lin, ), amurensin G (Kim, Kim, Lee, et al, ), volasertib (Jeon et al, ), temozolomide (TMZ) (Zhitao, Long, Jia, Yunchao, & Anhua, ), chalcone‐24 (Xu et al, ), gingerol (Lee, Kim, Jung, Lee, & Park, ), triptolide (Chen et al, ), AKT inhibitor API‐1 (Li, Ren, et al, ), smac mimetic compounds (SMC) (Cheung et al, ), dicoumarol (Park, Min, Choi, & Kwon, ), partenolide (Trang et al, ), Pyrrolo‐1, 5‐benzoxazepine (PBOX) (Nathwani et al, ), embelin (Siegelin, Gaiser, & Siegelin, ), myricetin (Siegelin, Gaiser, Habel, & Siegelin, ), quercetin (Jung, Heo, Lee, Kwon, & Kim, ), silibinin (Son et al, ), epigallocatechin gallate (EGCG) (Abou El Naga et al, ), icariside II (Du et al, ), anisomycin (Seo et al, ), dioscin (Kim, Kim, Park, et al, ), celecoxib (Chen et al, ), micro RNA 126 (MiR‐126) (Zhang, Zhou, Zhu, & Yuan, ), gambognic acid (Ye et al, ), survivin inhibitor YM155 (Woo, Min, Seo, &...…”
Section: Intracellular Anti‐apoptotic Proteins As Targeted Therapymentioning
confidence: 99%